The experience at a New School Education with ‘abnormal’ children: Faria de Vasconcelos (1880-1939) in the context of special education - Martins, Ernesto Candeias (2018)
The author consider the role played by Faria de Vasconcelos in the construction of modern pedagogy, materialized in the School of Bierges (Belgium) ex perience, and the special education with school ‘abnormal’ children. Using her meneutic and historical-descriptive analysis on his pedagogical thought and action, the goals of this chapter are to deepen the experience with Bierges, integrated into the ideals of the new school, which involved students for inclusion, the power of initiative, observation, experimentation and integral culture, associating thought-action; to analyze the contributions to the education of pedagogical abnormal’ children and to schools, from mental and pedagogical reeducation. Teaching always included practical application, learning by inquiry, problem solving and working by doing, developing the basic dimensions of the child: physical, intellectual, moral and civic cooperation. This special attention given to the ‘abnormals’, who at the time had no special school, was a huge contribution to special education, conducting psych pedagogical examinations, diagnostics and interventions, which provided a useful guidance to schools and teachers. The proposals of A.S. Faria de Vasconcelos fit some guidelines of special education and psychological support.